View of the backside of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
The eastern side offers a view of the backside of the Mahakal Temple and the front of the Hazareshwar Temple. On the rear side of the Mahakal Temple, the eastern or main garbhagriha (sanctum sanctorum) is visible.